Assessing and Comparing the Role of Machine Learning (ML) and Supply Chain Management (SCM) Towards Enhancing E-Commerce - Wisetsri, Worakamol; Syam, Elgamar; Alanya-Beltran, Joel; Kulkarni, Gopal Ramchandra; Vardhan Reddy, R Krishna; Alam Sheikh, Mohammed Firdos (2022 2nd International Conference on Advance Computing and Innovative Technologies in Engineering (ICACITE), 2022)
The current dynamism of the business environment revolves around supply chain management as the Organisation are poised in procuring the raw materials, transport it to the warehouse for processing and then distributing to the customers. The time and effort involved in the distribution channels need to be reduced so that the customers get the products on time and will save more cost for the Organisation. The implementation of machine learning (ML) tools enables the management in using various technologies to track the purchase request, enable in monitoring the movement of goods on a real time basis and take proper action so that the products are delivered on time to the customers. The advent of internet has enabled the customers to procure goods and services through online and this has enabled in increasing the revenues and profitability of the business. Hence, the management are focused in using various technologies to strengthen their SCM so that the goods can be tracked on a real time basis and support in achieving the sustainable development. It can be regarded that the today's competitive environment enables in realizing the customer expectation in an effective manner, the impact of globalization has compelled many companies to be highly competent in servicing their customers effectively This study is more focused in understanding the impact of ML in enhancing the SCM operations in the Organisation, the current pandemic situation has forced companies to rethink their strategies on the supply chain management so as to enhance the performance, reduce cost and meet the needs of the customers in an effective manner. The paper enables in understanding the critical issues and analyses the association with the ecommerce for achieving sustainable development. The study will apply positivism research design as it supports the researcher to understand the area of study in a more elaborate manner, furthermore the researcher uses quantitative research tools for gathering the data and make profundo analysis so as to make appropriate understanding on the subject area. Also, the researcher uses both primary and secondary source for performing the study in an effective manner. The entire study will enable in apprehending the gaps in research which poised to compare the role of ML and SCM in enhancing e-commerce in the future business environment.